Etika Jual Beli Dalam Perlindungan Konsumen Pada Produk Palsu Di E-Commerce - Muhammad fachri; Dini khaerani; Kurniati (Al-Iqtisodiyah : Jurnal Ilmu Ekonomi dan Ekonomi Islam, 2026)
The growth of e-commerce platforms in Indonesia has indeed created significant space for trade activities, but at the same time, it has also given rise to new problems, particularly the widespread circulation of counterfeit products that can harm buyers. This study seeks to examine how the principles of Islamic transaction ethics can serve as a basis for strengthening consumer protection in digital transactions. This research was conducted through a literature review, examining primary sources such as the Quran, hadith, and the thoughts of Islamic scholars. This research was supplemented by supporting materials in the form of books, scientific articles, and national laws and regulations, including Law Number 8 of 1999 concerning Consumer Protection. This study found that Islam teaches the values ​​of honesty, clarity of information, mutual consent, and prohibits practices that involve elements of uncertainty, fraud, and usury. These principles align with positive legal regulations aimed at protecting consumer rights and security. Therefore, the application of Islamic transaction ethics in the digital trading environment is considered capable of strengthening consumer protection while building an e-commerce ecosystem that is safer, fairer, and in accordance with Islamic guidance. Abstrak Pertumbuhan platform jual beli e-commerce di Indonesia memang telah memberikan ruang yang signifikan bagi aktivitas perdagangan, tetapi di saat yang sama, hal ini juga menimbulkan permasalahan baru, terutama maraknya peredaran produk palsu yang dapat merugikan pembeli. Penelitian ini berupaya mengkaji bagaimana prinsip-prinsip etika muamalah Islam dapat menjadi dasar penguatan perlindungan konsumen dalam transaksi digital. Penelitian ini dilakukan melalui studi pustaka, dengan mengkaji sumber-sumber primer seperti Al-Qur'an, hadis, dan pemikiran para ulama. Penelitian ini dilengkapi dengan bahan-bahan pendukung berupa buku, artikel ilmiah, dan peraturan perundang-undangan nasional, termasuk Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen. Penelitian ini menemukan bahwa Islam mengajarkan nilai-nilai kejujuran, kejelasan informasi, kerelaan bersama, dan larangan praktik-praktik yang mengandung unsur ketidakpastian, penipuan, dan riba. Prinsip-prinsip ini selaras dengan peraturan hukum positif yang bertujuan untuk melindungi hak dan keamanan konsumen. Oleh karena itu, penerapan etika transaksi Islam dalam lingkungan perdagangan digital dinilai mampu memperkuat perlindungan konsumen sekaligus membangun ekosistem e-commerce yang lebih aman, adil, dan sesuai dengan tuntunan Islam.